Experimental Research on Key Factors Influencing the Expansion Performance of New Type Sealing Materials - Yaobin Li; Xin Guo; Sheng Xue; Chun-Shan Zheng; Maoliang Shen; Yang Xu (Advances in Civil Engineering)
To improve the borehole sealing effect, especially that of coal seam with low permeability and micro fissures, this paper takes the expansion rate of the sealing material as the response value and establishes the quadratic model embracing the expansion rate and various experimental factors by designing orthogonal experiments. The response surface is used to further determine the significance order of each key factor according to the expansion rate and adjust the admixture content to obtain the optimal ratio of the sealing material. For the research investigating a sealing material, the optimal ratio of the sealing material is obtained: the content of water reducing agent of 0.5%, the content of retarder of 0.04%, water-cement ratio of 0.8, and the content of expansion agent of 10%. At this time, the expansion rate reaches 3.136%. Besides, a scanning electron microscope is used to observe the microscopic morphology of the material. According to the scanning electron microscopy analysis of new borehole sealing materials, the surface of the new borehole sealing material shows no holes and possesses compactness; and a large amount of ettringite is formed on the surface of the hydration product of hardened cement slurry. The ettringite improves the expansibility of the material. The new sealing material provides a new idea for gas sealing, which is of great significance to improve the efficiency of borehole extraction, improve the utilization rate of resources, and prevent gas accidents.